Knowledge, attitudes, and practices of dairy farmers in the adoption of Brachiaria grass in Kenya - Maina, Kevin W.; Ritho, C.N.; Lukuyu, Ben A.; Rao, E.J.O.; Mugwe, J.G. (Elsevier, 2021)
This paper assesses farmers' knowledge, attitude and practices in the adoption of Brachiaria grass using a mixed-methods approach. Results indicate that farmers are aware of different improved forages they have adopted and their varieties. Results from the household survey on farmers' attitudes on the perceived benefits of Brachiaria indicates that adopters perceived Brachiaria to increase milk production and fodder availability. Thus, farmers' perception is a function of awareness and access to information and is one of the factors limiting adoption. The study recommends investment in training and extension services to farmers in order to up-scale adoption.